2020
DOI: 10.1093/ecco-jcc/jjaa097
|View full text |Cite
|
Sign up to set email alerts
|

Highly Bioavailable Curcumin Derivative Ameliorates Crohn’s Disease Symptoms: A Randomized, Double-Blind, Multicenter Study

Abstract: Abstract Background & Aims The new curcumin derivative Theracurmin® has a 27–fold higher absorption rate than natural curcumin powder. Theracurmin® is an inhibitor of nuclear factor-κB, which mediates the expression of inflammatory cytokines. The effect of Theracurmin® on inflammatory bowel disease in humans has not been explored; therefore, we investigated the efficacy and safety of Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 28 publications
0
69
0
Order By: Relevance
“…The clinical reduction observed at 4, 8, and 12 weeks was 35%, 40%, and 40%, respectively, which was considerably higher than in the placebo group. Theracurcumin also exhibited a decrease in the severity of CD and stronger endoscopic reduction levels in the theracurcumin group (15% compared to 0% in the placebo-treated groups), suggesting the potential of using theracurcumin to ameliorate the CD [ 130 ].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…The clinical reduction observed at 4, 8, and 12 weeks was 35%, 40%, and 40%, respectively, which was considerably higher than in the placebo group. Theracurcumin also exhibited a decrease in the severity of CD and stronger endoscopic reduction levels in the theracurcumin group (15% compared to 0% in the placebo-treated groups), suggesting the potential of using theracurcumin to ameliorate the CD [ 130 ].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In the prevention setting, from the 15 studies that met all five quality criteria, 10 had positive clinical outcomes. These outcomes related directly to efficacy [12] , symptom improvement [15,20,25,28] , durability of clinical response [22] , clinical remission [23,29,30] , and assessment by biomarker changes. [26] This provides encouraging information to suggest potential for positive patient benefit within the oral lichen planus, oral leucoplakia, ulcerative colitis, Crohn's disease, and oral submucous fibrosis settings.…”
Section: Discussionmentioning
confidence: 99%
“…The Crohn's disease activity index (CDAI) is a seven-criteria disease activity index including frequency of liquid stools, abdominal pain, general wellbeing, presence of complication, use of medication for diarrhoea, abdominal mass, haematocrit, and deviation from standard weight [81]. Administration of Theracurmin, which has increased bioavailability in comparison with standard curcumin, resulted in a significant reduction in CDAI [54] compared with a non-significant reduction with standard curcumin [43]. One study found no change in CDAI in CD or ulcerative colitis clinical activity index (UCAI) in UC with moderate red wine consumption [53].…”
Section: (Poly)phenols and Symptoms In Inflammatory Bowel Disease And Irritable Bowel Syndromementioning
confidence: 99%
“…Extra virgin olive oil administration resulted in a significant reduction in reports of constipation [47]. One study explored individual gastrointestinal symptoms in CD and found supplementation with Theracurmin significantly reduced stool frequency and demonstrated a trend in reduced abdominal pain [54].…”
Section: (Poly)phenols and Symptoms In Inflammatory Bowel Disease And Irritable Bowel Syndromementioning
confidence: 99%
See 1 more Smart Citation